Silent killer presenting as isolated oculomotor nerve palsy - A., Mary Stephen; P., Jayasri; J., Harigaravelu P.; ., Baranitharan (International Journal of Advances in Medicine, 2022)
Head trauma can result trivial to life threatening manifestations to a person. Subdural hemotoma is characterised by accumulation of blood in subdural space, in most cases it is a serious condition and requires prompt diagnosis and treatment for the same to provide good outcome. Large collection, mid line shift, brain herniation associated with subdural hematoma is associated with increased morbidity and mortality. However, if the collection is minimal or is places like tentorium cerebelli may not have the typical presentation and if it’s picked up using the subtle signs the devastating sequelae can be prevented. We report a 19 years old male with head trauma presenting with features of right-side isolated oculomotor nerve palsy who eventually found to have tentorial subdural hemotoma in imaging which has been intervened and complications were avoided.